Information Systems in Higher Educational Institutions - Tressa, Neethu (International Journal of Computer Sciences and Engineering, 2018)
Nowadays higher education has been a prime need for all for a better future. As the higher education is globally expanded to a great extend, anybody can attain this from anywhere. But still, the educational institutions have to play a big role to provide the students all the necessary resources on time for them to make their education a quality one. In such a situation, it has been proved that information systems can do wonders. This paper is intended to show how to help an institution in storing, analyzing, monitoring and improving all the academic and co-academic information and status in an efficient way. The major pillars of an education system are the students, their parents, teachers and the management. They are the ones who can point out the actual needs related with an educational institution. If there is an efficient information system that can assist an institution in identifying and evaluating the needs and corresponding solutions, the management will be able to easily get adapted to the new global changes.